Navigating Chronic Disease Management with Digital Healthcare Solutions amidst the COVID-19 Pandemic: A Systematic Literature Review - Vratimos, Achillefs; Champilomatis, Ilias; Farantos, Georgios (European Scientific Journal, ESJ, 2024)
Purpose: The purpose of this paper is to critically evaluate data collected from various studies on Chronic Disease Management during the COVID-19 pandemic and the emergence of Digital Healthcare as a means of providing innovative approaches to manage chronic diseases. Methodology: A systematic literature review was applied. Studies were found after a search in the Pubmed database with no publication date time limit, given that COVID–19 emerged in 2019. A Prisma diagram was created to record the way and the criteria by which we included and excluded studies for our research. Out of the 567 records identified through various sources 85 were used for a qualitative synthesis. Results: During the first wave of the pandemic, a significant reduction or complete cancellation of scheduled health appointments was observed. Shortages of medication used to manage chronic conditions were also observed at the beginning of the COVID-19 pandemic due to global supply chain disruptions. Governments acted rapidly at the beginning of the pandemic to promote the use of teleconsultations by introducing enabling legislation and revising laws ensuring continuity of care for people with chronic diseases, thus transitioning rapidly to remote care and monitoring. Conclusion: Telemedicine and involving community pharmacists in chronic patient management are key for sustained adherence. Long-term policies are vital to prevent pandemic-driven health disparities. Lessons should be derived for future preparedness, managing subsequent waves, and ensuring testing in primary care.